Innovation systems and value chain approaches for dairy development - International Livestock Research Institute (International Livestock Research Institute, 2010)
Speaking at the opening of the National dairy forum on 23 November 2010, Berhanu G/Medhin said that the value chain concept is quite popular and many development and research projects are following this approach. He emphasized that when we do research or development interventions we need to carefully analyze the value chain on the particular commodity and also try to identify the priority problems along the value chain, mapping the innovation system for the particular problem.